PENGARUH METODE CERAMAH INTERAKTIF TERHADAP KOMPETENSI BAHASA INGGRIS SISWA SEKOLAH DASAR DI ASAHAN - Sahmiral Amri Rajagukguk; Diah Safithri Armin; Agung Arif Hakim Batubara (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study investigates the effectiveness of the interactive lecture method in improving English language acquisition among primary school students in Asahan Regency, North Sumatra. The purpose of the study was to evaluate the difference in learning outcomes between students taught using the interactive lecture method and students taught using conventional methods. The research method used was an experiment with a pre-test and post-test design, involving 20 fifth grade students who were divided into two groups: control and treatment. The results showed that the treatment group showed a significant increase in scores compared to the control group. The conclusion of the study underlines that the interactive lecture method is more effective in improving students' English proficiency. This study highlights the importance of using the interactive lecture method in English language teaching to improve students' learning outcomes, and suggests further research with larger samples and different treatment durations.